Pediatric Medical Spanish Vignettes - Angelika Rampal; Connie Wang; Jennifer Kalisvaart (Association of American Medical Colleges, 2009)
Abstract This resource provides six pediatric vignettes to be used for teaching and learning of basic medical Spanish. The role-plays are designed for use in group settings such as a noon conference or morning report, where residents or students interested in the Spanish language can pair off and practice their skills. Ideally, each pair will consist of one experienced Spanish speaker and one less experienced learner. One person plays the parent/patient while the other plays the doctor. The vignettes are written in Spanish with English translations. Each one may only take a few minutes to read through, but they are intended to be launching pads for further conversational Spanish. The role-plays consist of three well-child visits and three urgent care visits. The well visits include a newborn visit, a 2-month well-child check, and a 1-year well-child check. The urgent care visits include asthma, gastroenteritis, and upper respiratory infection. Many trainees see Spanish-speaking patients regularly and are interested in improving their Spanish skills. While these vignettes do not offer a complete course in Spanish, they can be used as an adjunct for those interested in taking additional time to focus on their Spanish communication. One of the participants in each role-play should have some experience with Spanish in order to help lead the conversation and teach the less experienced member of the team. There should also be a group facilitator who speaks Spanish and can help to answer questions that may arise.